The Organizational Contribution of the PMO: An Assessment Using Structural Equation Modeling - El Yacoubi, Zouheir; Jahidi, Rachid (European Scientific Journal, ESJ, 2024)
This research is part of a thesis project that includes two main phases, and it aims to develop and examine a conceptual model to understand and verify the contribution of the PMO to the performance of Moroccan organizations as well as to their level of project management maturity in terms of organization and practices. Thus, the main objectives of this research are: (1) examine the PMO contribution to organizational performance and project management maturity, but also (2) contribute to the solidification of the theoretical basis of the project management school. For this, a quantitative approach was adopted, where a questionnaire was administrated online for three consecutive months. Firstly, the president of the PMI Moroccan chapter was contacted to request their collaboration. Secondly, a direct interaction was carried out with people evolving in project management within organizations that have a Project Management Office (PMO) and who could answer the questionnaire through the professional network "LinkedIn". Two hundred and five (205) responses were received, of which seventy-six (76) were discarded because the respondents declared the non-existence of a PMO within their organizations or it exist for less than three years. Finally, one hundred and twenty-nine (129) responses were considered usable and represent our final database from which we proceeded to a set of analyzes and tests. Two-stage data analysis was followed. First, a descriptive and exploratory analysis of the data collected was performed using SPSS. Next, a confirmatory analysis using structural equation modeling was carried out with the help of SmartPLS to examine the validity of the constructs of the model and to test the hypotheses. The results of this study provide a solid basis for linking PMO functions to organizational contributions. The study concluded that the PMO through its functions contributes to organizational performance and project management maturity. It also highlights the mediating effect of project management maturity. However, the possible moderating effect of PMO type on structural relationships could not be verified.